Who Teaches the Teachers? A Rct of Peer-to-Peer Observation and Feedback in 181 Schools - Gillian Wyness; Richard Murphy; Felix Weinhardt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
It is well established that teachers are the most important in-school factor in determining student outcomes. However, to date there is scant robust quantitative research demonstrating that teacher training programs can have lasting impacts on student test scores. To address this gap, we conduct and evaluate a teacher peer-to-peer observation and feedback program under Randomized Control Trial (RCT) conditions. Half of 181 volunteer primary schools in England were randomly selected to participate in the two year program. We find that students of treated teachers perform no better on national tests a year after the program ended. The absence of external observers and incentives in our program may explain the contrast of these results with the small body of work which shows a positive in uence of teacher observation and feedback on pupil outcomes.
Keywords: I21; I28; M53; 330; education; teachers; rct; peer mentoring